ANALISA KEANDALAN BANGUNAN PADA RUMAH SUSUN MAHASISWA ST. TERESA AVILA, SEMARANG - Evita Sekarsari, Beatrix; Rosaline Tobing, Rumiati (Jurnal Riset Arsitektur, 2022)
Abstract - College is a place for most students to study higher. Many students who come from outside the city or region look for schools and colleges in cities that are not their hometowns. So they have to find a place to stay to rest in their daily lives. The government helps the housing needs for students by building student flats or better known as dormitories in locations close to schools or colleges. In the utilization, use and management of dormitories, there are often several room changes as a result of the need for facilities and infrastructure. Changes in the function of the room can reduce the reliability value if done without taking into account several aspects. Assessment of building reliability is an important factor in checking the condition of a building. The purpose of this research is a study of the analysis of building reliability in the field of architecture to the student flats of St. Teresa Avilla, Semarang after 5 (five) years of residence. Does it still meet the applicable standards and regulations or the reliability values ​​are no longer valid. The research method used is descriptive and qualitative based on the physical conditions at the time of the research. And then the physical condition of the building is reviewed based on applicable regulations and existing theories. It can be concluded that there are several rooms that no longer meet the building reliability requirements, but most of them are still very feasible and in accordance with the needs. Suggestions can also be given to improve so that the condition and reliability values ​​can be maintained. Keywords: flat, building reliability, reliability evaluation